Genetics of Reproductive Aging from Gonadal Dysgenesis through Menopause - Desai, Swapna; Rajkovic, Aleksandar (Seminars in Reproductive Medicine, 2017)
Reproduction is essential for the survival of the species and is influenced by external factors such as smoking and exposure to chemotherapy as well as chronic disorders such as obesity and autoimmunity. Reproductive senescence, such as menopause, is also dependent on multiple intrinsic genetic factors. Reproductive aging is not isolated from an overall aging process, and several studies strongly support the link between the early age of menopause and mortality. The extreme form of reproductive aging is primary ovarian insufficiency (POI) with prevalence ranging from 1 to 5% of the female population. POI has been shown to have long-term consequences on overall health. POI and age of menopause have a significant hereditary component. The population-based genome-wide association studies have identified 44 genomic loci to associate with age of menopause, and 29 of 44 loci harbor DNA damage response genes. Recent application of whole exome sequencing on carefully selected families with POI has also revealed a significant contribution of DNA damage response genes. The inability to repair the DNA damage in both somatic and germ cells might be a predisposing factor for the link between reproductive and overall aging in a subset of individuals with POI. The aim of this review is to characterize recent advances in the genetics of POI and its link with overall health.
Keywords: ovarian reserve; menopause; primary ovarian insufficiency; DNA damage response genes